Perceptions and attitudes of older adult women on the family care and support of adult children in marginalized families - Aristorenas, Christiane Nicole F.; Cabal, Mary Angeline L.
This research examined the perspectives and attitudes of Filipino older adult women on their adult childrens family care and family support. This study aimed to identify the family care and support the adult children provide for the older adult women, and describe the perceptions and attitudes of older adult women toward all these care and support provided. The respondents of the study are 20 Filipino older adult women from marginalized families aged 65 to 75 years old. They underwent individual in-depth interviews. The results revealed that Filipino older adult women receive family care and family support in the physical, socio-emotional, medical and nutritional, and financial aspects of their lives. Generally, Filipino older adult women experience both happiness and contentment towards these different kinds of family care and family support they receive from their adult children despite coming from marginalized families.